Practice research enabler: Enabling research in a social work practice context. (July 2019) - Miller, Keith
Practitioners are curious people but have become increasingly estranged from investigation and the research process. A false divide has developed wherein knowledge gained from practice is considered by some as inferior to knowledge constructed by academics. The concept of phronesis, as practical wisdom, can provide a link to give a legitimacy to practice research. One difference between academic research and practice research is in the collaborative relationship between practitioner and researcher, a true engagement with equal partners. The academic can be seen as a practice research enabler who facilitates the knowledge which practitioners develop in a localized setting and situates it in a broader theoretical perspective. As a research enabler, a researcher brings academic expertise to supplement the practice expertise of the practitioner to develop new knowledge. In a series of examples, and using a critical discourse analysis approach, the author critically assesses his own practice to identify an unsuccessful, a partially successful and a successful example of being a practice research enabler.